2014
DOI: 10.4049/jimmunol.1303214
|View full text |Cite
|
Sign up to set email alerts
|

Human Regulatory B Cells Combine Phenotypic and Genetic Hallmarks with a Distinct Differentiation Fate

Abstract: Regulatory B cells (B-reg) produce IL-10 and suppress inflammation in both mice and humans, but limited data on the phenotype and function of these cells have precluded detailed assessment of their contribution to host immunity. In this article, we report that human B-reg cannot be defined based on a phenotype composed of conventional B cell markers, and that IL-10 production can be elicited in both the CD27+ memory population and naive B cell subset after only a brief stimulation in vitro. We therefore sought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…2) (33). Note that these B cells, however, expressed a higher level of Irf4 transcripts following stimulation, a gene recently identified as one of the most significantly upregulated in IL-10 + -producing B cells (12). These differences were lost by the addition of CpG (data not shown), suggesting that CpG may induce a too strong stimulation or that the effects observed were specific to CD40 stimulation.…”
Section: Igmmentioning
confidence: 81%
See 2 more Smart Citations
“…2) (33). Note that these B cells, however, expressed a higher level of Irf4 transcripts following stimulation, a gene recently identified as one of the most significantly upregulated in IL-10 + -producing B cells (12). These differences were lost by the addition of CpG (data not shown), suggesting that CpG may induce a too strong stimulation or that the effects observed were specific to CD40 stimulation.…”
Section: Igmmentioning
confidence: 81%
“…Regulatory B cells may be composed of cells with a heterogeneous phenotype and present at various steps of differentiation. Indeed, it has been suggested that regulatory B cells acquired their fully suppressive phenotype following reencounter with the specific Ags at the plasmablast/ plasma cell differentiation step by acting through the secretion of a high level of immunosuppressive cytokine such as IL-10 or IL-35 (9,12,38,39). We observed in a mouse skin graft model that LF15-0195 immunosuppressor induced during treatment a strong drop in the new T1 emigrants B cells in blood that were then restored following treatment cessation (E. Chiffoleau, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, a fair characterization given the current knowledge of the Breg phenotype. In fact, several phenotypes have been reported to define Bregs in mice and humans, raising the possibility that distinct subsets of Breg exist in different tissues and compartments in vivo [7,11].…”
Section: Regulatory B Cells Phenotype and Functionmentioning
confidence: 99%
“…Recently, a connectivity map analysis revealed that IL-10? B cells are those specifically undergoing differentiation toward a germinal center B cell fate [11]. These cells were identified as CD11c-negative B cells, had suppressive activity, and were unable to efficiently differentiate into plasma cells.…”
Section: Regulatory B Cells Phenotype and Functionmentioning
confidence: 99%